Fermented mahua oil cake in the diet of Labeo rohita: effects on growth performance, digestive enzyme activity and immune response - Das, Krushna Chandra; Mohanty, Aradhana; Swain, Priyabrat; Routray, P.; Kumari, Rakhi (Frontiers in Marine Science, 2024)
Market instability, increased competition, escalating price and reduced availability of conventional ingredients warrants the researchers to rely on alternative feed ingredients. This approach may help in producing aqua feeds in a sustainable and cost-effective way to accomplish the global food and nutritional securities. Mahua oil cake (Bassia latifolia) is an underutilized non-conventional ingredient that holds promise for incorporation into aqua feed following nutrient enhancement by solid-state fermentation. A five-month pond feeding trial was carried out to investigate the effects of Sachharomyces cerevisiae and Bacillus subtilis fermented mahua oil cake (MOC) on the production performance, nutrient utilization, digestive capacity, and innate immunological responses of Labeo rohita fingerlings. For this, two iso-nitrogenous feed were formulated and prepared incorporating fermented MOC at different levels i.e. 0 and 40 percentage replacing soybean meal and other feed ingredients and fed to rohu fingerlings of two treatment groups in pond culture for 5 months duration. Improved growth performance, feed conversion ratio, feed intake, protein efficiency ratio and digestive capacity were observed in fish fed diets with 40 percent of fermented MOC compared to control. Innate immune responses parameters (respiratory burst activity, myeloperoxidase, lysozyme and hemaglutination activities) were significantly higher (P < 0.05) in fishes fed with fermented MOC. Therefore, we conclude incorporation of solid state fermented mahua oil cake up to 40% level in diet of L. rohita fingerlings in pond culture without any adverse effects on growth, nutrient utilization and innate immune response.